Influence of tactical behaviour on running performance in the three most successful soccer teams during the competitive season of the Spanish first division - Asian-Clemente, J.; Suarez-Arrones, L.; Requena, B.; Santalla, A. (Journal of Human Kinetics, 2022)
The purpose of this study was to analyze the influence of tactical behavior on physical performance of the three best Spanish soccer teams. Team 1 employed a 1-4-4-2 formation with compact defence and direct attacks, Team 2 employed an indirect style of play with a 1-4-3-3 formation and Team 3 used a 1-4-3-3 formation with elaborate attacks and strong counter-attacks. 816 individual situations of 54 professional soccer players categorized as fullbacks (FB), central defenders (CD), central midfielders (MF), wide midfielders (WM), and strikers (S) were included in the analysis. Their performance was examined with a player-tracking system. The analyzed variables included total distance covered, distance covered above 14, 21 and 24 km·h -1, as well as distance covered in possession of the ball and without possession of the ball. Team 2 covered a substantially lower distance >14 km·h-1 than Team 1 and substantially lower distances >14, >21, and >25km·h -1 than Team 3. No differences in running activity were found between Teams 1 and 3. However, there were substantial differences between the specific positions of the three teams. CD in Team 1 covered the lowest distance by a substantial margin in almost all variables analysed, whereas MF travelled substantially greater distances than did other positions. WM in Team 1 covered the greatest distance >18 and >21km·h- 1 , while S in Team 2 had the lowest distance covered in almost all the variables, and FB in Team 3 showed the lowest total distance covered and distance covered >14km·h-1. WM in Team 2 had the greatest distance covered in possession, while S in Team 3 had the greatest distance covered out of possession. The results indicate that different team formations and associated tactical demands have a significant influence on running performance.